Potential effects of assisted reproductive technology on telomere length and telomerase activity in human oocytes and early embryos - Betul Tire; Saffet Ozturk (BMC, 2023)
Abstract Telomeres are repetitive DNA sequences at eukaryotic chromosome ends and function in maintaining genome integrity and stability. These unique structures undergo shortening due to various factors including biological aging, consecutive DNA replication, oxidative stress, and genotoxic agents. Shortened telomeres can be lengthened by the enzyme telomerase and alternative lengthening of telomeres in germ cells, early embryos, stem cells, and activated lymphocytes. If telomeres reach to critical length, it may lead to genomic instability, chromosome segregation defects, aneuploidy, and apoptosis. These phenotypes also occur in the oocytes and early embryos, produced using assisted reproductive technologies (ARTs). Thus, a number of studies have examined the potential effects of ART applications such as ovarian stimulation, culture conditions, and cryopreservation procedures on telomeres. Herein, we comprehensively reviewed impacts of these applications on telomere length and telomerase activity in ART-derived oocytes and embryos. Further, we discussed use of these parameters in ART centers as a biomarker in determining oocyte and embryo quality.